Discovering your soul signature : a 33-day path to purpose, passion, & joy - Desai, Panache (Spiegel & Grau, 2014)
Offers a thirty-three day set of passages to be read at morning, noon, and night intended to remove the emotional obstacles that keep people from expressing their true selves and living a life of authenticity, purpose, and passion.